A Bibliometric on Corporate Finance Talent Development - Loso Judijanto; Putri Ridhotul Uliyah (Westscience Press, 2026)
This study conducts a bibliometric analysis on the development of talent in corporate finance, examining the evolution, intellectual structure, and emerging trends within this research area. Using data collected from Scopus, the study highlights key themes, influential publications, and leading contributors in the field. The analysis reveals the increasing focus on the integration of sustainable finance practices, corporate strategy, and digital technologies such as fintech, which are reshaping the competencies required of corporate finance professionals. The findings suggest that while traditional financial expertise remains foundational, the growing importance of environmental, social, and governance (ESG) considerations, along with technological advancements, are shaping the future of corporate finance talent development. This bibliometric overview provides valuable insights into the evolving landscape of corporate finance education and skill development, offering guidance for future research and professional practice.